2012
DOI: 10.3109/00365521.2012.668932
|View full text |Cite
|
Sign up to set email alerts
|

Erosive esophagitis may be related to small intestinal bacterial overgrowth

Abstract: Subjects with EE had a higher prevalence of SIBO, as assessed by the lactulose hydrogen breath test, with respect to a control group. These findings may suggest that EE is associated with SIBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…In addition, some authors observed a higher frequency of bacterial overgrowth of the small intestine in patients with esophagitis (25) . Other study observed that the colonic fermentation of non-digestible carbohydrates by intestinal microbiota caused a higher rate of transient relaxation of the LES, a larger number of episodes of acid reflux, and symptoms of GERD (17) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors observed a higher frequency of bacterial overgrowth of the small intestine in patients with esophagitis (25) . Other study observed that the colonic fermentation of non-digestible carbohydrates by intestinal microbiota caused a higher rate of transient relaxation of the LES, a larger number of episodes of acid reflux, and symptoms of GERD (17) .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kim et al demonstrated that SIBO is more prevalent in patients with GERD (assessed with the LBT) than in the general population [47].…”
Section: Association Between Sibo and Other Nosological Entitiesmentioning
confidence: 99%
“…Patients with erosive esophagitis had SIBO more frequently than controls (65% vs 31%; OR = 4.0)[ 99 ].…”
Section: Other Digestive Diseasesmentioning
confidence: 99%